1963
DOI: 10.1139/b63-152
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Light Intensity and Temperature on Floral Initiation and Inflorescence Development of Marquis Wheat

Abstract: Under continuous illumination, floral initiation was earlier with each increase in light intensity from 200 to 2500 ft-c, and with each increase in temperature between 10 and 30 °C. This effect of light intensity is attributed to promotion of floral initiation by energy in the far-red (730 mμ).The rate of formation of leaf primordia was accelerated by increases in light intensity to a greater extent than floral initiation, so that the final leaf number on the main shoot was greatest for the plants grown at hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
1
3

Year Published

1974
1974
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(31 citation statements)
references
References 12 publications
1
26
1
3
Order By: Relevance
“…They found that a rise in temperature from 13°to 21°C produced a decline in yield which was attributed to a decrease in leaf size as well as to thinner and shorter culms. For barley, however, the optimum temperature obviously is much lower than the 20°C claimed by Friend (1966) to be the optimum for wheat.…”
Section: Discussionmentioning
confidence: 65%
See 3 more Smart Citations
“…They found that a rise in temperature from 13°to 21°C produced a decline in yield which was attributed to a decrease in leaf size as well as to thinner and shorter culms. For barley, however, the optimum temperature obviously is much lower than the 20°C claimed by Friend (1966) to be the optimum for wheat.…”
Section: Discussionmentioning
confidence: 65%
“…The percentage proportion of leaves was larger at the higher temperature, as was also found with wheat (Friend 1966). In contrast, the percentage of culms was at the lower temperature higher than at the higher temperature; Langer (1963) considers this a common phenomenon in all graminaceous plants.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…In Marquis spring wheat, Friend et al (1963) found early floral initiaton at higher temperatures was due to increased production of flower-inducing substances or increased sensitivity of meristernatic cells to hormones. Hamner and Bonner (1938), examining the interrelation ship of temperature and photoperiod upon floral initiation in Xanthium, found that plants given one short photoperiod at greenhouse temperature, then one long dark period (more than 8 hours) at 21°-32° C developed floral primordia, whereas at 4® C, seven dark periods were required.…”
Section: Temperature and Morphological Developmentmentioning
confidence: 99%